Can public health reconcile profits and pandemics? An analysis of attitudes to commercial sector engagement in health policy and research. - Jeff Collin; Sarah E Hill; Mor Kandlik Eltanani; Evgeniya Plotnikova; Rob Ralston; Katherine E Smith (PLoS ONE)
Background Public health's terms of engagement with unhealthy commodity industries (alcohol, tobacco and ultra-processed food and drinks) have become increasingly contested in policy and research. We sought to identify approaches that could attract consensus support within and across policy domains. Methods Using snowball sampling, we undertook an online survey of 335 health researchers, advocates and policymakers, in 40 countries, assessing responses to stated principles, claims and recommendations for engaging with unhealthy commodity industries in relation to key policy and research initiatives. Results Most respondents identified a fundamental conflict between industry interests and public health objectives for all three industries, with agreement greatest in relation to tobacco and weakest for food. This pattern was replicated across diverse questions regarding potential forms of engagement, including in rejecting voluntarism and partnership approaches to health policy. While awareness of tobacco industry tactics to influence policy and research was higher than for alcohol and food, most respondents rejected the view that the influence of the latter was less significant for public health. Proposals that health and research organisations should divest their funds attracted less support with respect to food, while restricting publication of industry-funded research in academic journals was the issue that most divided opinion. Respondents reported most difficulty in answering questions about the food industry. Conclusions The strong consensus around restricting interactions with the tobacco industry supports increased implementation of the WHO Framework Convention on Tobacco Control's conflict of interest provisions. There is strong support for the extension of such practices to the alcohol industry, challenging current norms. More mixed responses indicate a need for greater clarity in defining the food industry, and for research analyzing links, similarities and differences across different types of unhealthy commodity producers. Partnership approaches to addressing non-communicable diseases seem incapable of attracting widespread support across public health, challenging practice in many contexts.